Deflection calculation method for UHPC composite beams considering interface slip and shear deformation. (15th April 2023) - Cao, Lei; Zeng, Dan; Liu, Yang; Li, Zhaochao; Zuo, Hao
Highlights: The flexural behavior of steel-GFRP strips-UHPC composite beam under the positive moment was investigated The bending stiffness, ultimate bearing capacity, deflection and slip of the two composite beams were comparatively analyzed. The analytical solution of mid-span deflection considering both the shear deformation and the interface slip was derived. The theoretical calculation method of ultimate flexural bearing capacity of the two UHPC composite beams are obtained. Abstract: The mid-span deflection is an essential index for evaluating the safety of bridge safety and service life. In contrast, the existing deflection calculation methods cannot accurately predict the deflection of ultra-high performance concrete (UHPC) composite beams. The flexural behavior of steel-glass fiber reinforced polymer (GFRP) strips-UHPC composite beam under a positive bending moment was investigated and compared with that of the steel-UHPC composite beam. The flexural behavior of UHPC composite beam was analyzed and discussed in terms of failure mode and mechanism, mid-span load-deflection response, changing laws of cross-section strain and interface slip. The deflection calculation method for the UHPC composite beams considering interface slip and shear deformation was derived. Moreover, a calculation method of ultimate bearing capacity for the UHPC composite beams is developed. The results showed that all the UHPC composite beams failed because of yielding of steel beam, and the influence of GFRP strips on the flexural behavior of steel-UHPC composite beam was very small. The theoretically calculated results of the mid-span deflection and ultimate bearing capacity for the UHPC composite beams were in good agreement with the experimental results and have higher accuracy.